Curriculum Management of Local Content in Fostering Religious Behavior: A Study at Madrasah Aliyah - Zamroni, M. Afif; Supriyanto, Heri; Fatikh, M. Alfin; Sirojuddin, Akhmad; Sholihah, Maidatus; Alai, Ashimatul (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This study investigates the management of local content curriculum in shaping religious behavior at MA Raden Paku Wringinanom. Specifically, the research addresses three key questions: (1) How is the local content curriculum planned to foster religious behavior at MA Raden Paku Wringinanom? (2) How is the local content curriculum implemented to shape religious behavior at MA Raden Paku Wringinanom? (3) What are the outcomes of the local content curriculum in fostering religious behavior at MA Raden Paku Wringinanom? The objectives of this study are to: (1) examine the planning of the local content curriculum, (2) explore the implementation process, and (3) analyze the outcomes in shaping religious behavior at MA Raden Paku Wringinanom. This research employs a qualitative method with descriptive analysis, utilizing an interactive model. The data analysis involves stages of data reduction, data display, and conclusion drawing. After collecting and categorizing the data, the researcher provides an in-depth description before concluding the findings based on available sources. The results of this study are as follows: (1) The planning of the local content curriculum involves adherence to the School Work Plan (RKT) and the Madrasah Work Plan and Budget (RKAM) to define local content programs, select subjects, assign teachers, and determine learning resources and funding. (2) The implementation phase includes syllabus review, lesson plan (RPP) development, and assessment. (3) The outcomes of the local content curriculum include program-specific local content initiatives and the evaluation of student learning outcomes.